Reduction of Fe Using Advanced Oxidation Processes (AOPs) and Electromagnetic Water Treatment (EWT) - Veny Luvita; Novan Agung Mahardiono; Hanif Fakhrurroja; Adi Waskito (Dept. of Chemical Engineering, Diponegoro University, 2021)
The processing on water treatment in this research is carried out by using two combination methods of Advanced Oxidation Processes (AOPs) and Electromagnetic Water Treatment (EWT). The application of AOPs method is one of alternative to remove heavy metals while the application of EWT method is to improve water quality and to prevent the using of expensive chemicals or corrosive substances. The using of chemicals can cause new problems that endanger human health or damage the environment. This paper presents the advantage of the combining these methods is the high ability to process contaminated water into clean water. AOPs and EWT system configuration is needed to determine the effectiveness of the processing system, especially in removing heavy metal minerals such as iron (Fe). Based on the efficiency result, the configuration by using AOPs + EWT reduces the iron (Fe) mineral content by 99,33% and increases the pH value by 6.09.Keywords: water; treatment; substances; metal; mineral